Diffusion imaging of cerebral diaschisis in childhood arterial ischemic stroke. Issue 9 (December 2016) - Kirton, Adam; Williams, Elizabeth; Dowling, Michael; Mah, Sarah; Hodge, Jacquie; Carlson, Helen; Wei, Xing-Chang; Ichord, Rebecca; ,
Background: Diffusion-weighted imaging magnetic resonance imaging may detect changes in brain structures remote but connected to stroke consistent with neuropathological descriptions of diaschisis. Early diffusion-weighted imaging demonstrates restriction in corticospinal pathways after arterial ischemic stroke of all ages that correlates with motor outcome. Aim/hypothesis: We hypothesized that cerebral diaschisis is measurable in childhood arterial ischemic stroke and explored associations with outcome. Methods: This sub-study of the validation of the Pediatric NIH Stroke Scale study prospectively enrolled children with acute arterial ischemic stroke and both acute and early follow-up (5–14 days) diffusion-weighted imaging. Inclusion criteria were (1) unilateral middle cerebral artery arterial ischemic stroke, (2) acute and subacute diffusion-weighted imaging ( b = 1000), and (3) 12 month neurological follow-up (Pediatric Stroke Outcome Measure). A validated method using ImageJ software quantified diffusion-weighted imaging diaschisis in anatomically connected structures. Diaschisis measures were corrected for infarct volume, compared to age, imaging timing, and outcomes (Chi square/Fisher, Mann–Whitney test). Results: Nineteen children (53% male, median 8.1 years) had magnetic resonance imaging at medians of 21 and 168 h post-stroke onset. Diaschisis was common and evolved over time, observed in one (5%) on acute but eight (42%) by follow-up diffusion-weighted imaging. Thalamic and callosal diaschisis were most common (5, 26%). Estimates of perilesional diaschisis varied (54 ± 18% of infarct volume). Children with diaschisis tended to be younger (7.02 ± 5.4 vs. 11.82 ± 4.3 years, p = 0.08). Total diaschisis score was associated with poor cognitive outcomes ( p = 0.03). Corticospinal tract diaschisis was associated with motor outcome ( p = 0.004). Method reliability was excellent. Conclusions: Diffusion-weighted imaging diaschisis occurs in childhood arterial ischemic stroke. Mistaking diaschisis for new areas of infarction carries important clinical implications. Improved recognition and study are required to establish clinical relevance.